Importance of supporting survivors through a mental health and psychosocial support lens to ensure justice: a case study of girls who were raped and abused in a childcare home in Nepal. Issue 1 (March 2017) - Guragain, Bhushan; Ghimire, Lajina
Abstract : This field report from Nepal highlights the importance of mental health and psychosocial support in ensuring justice for survivors of sexual violence and abuse. It solidifies how psychosocial support can help to improve the low rate of reporting of sexual violence and lead to higher rates of convictions of perpetrators. The Centre for Victims of Torture Nepal has supported more than 150 survivors of torture, conflict and rape to receive justice in the courts through a holistic approach with mental health and psychosocial support at its core. The organisation is presently pursuing four new cases of child sexual abuse, occurring after the 25 April 2015 earthquake, with a similar approach. Challenges remain in providing justice to survivors of violence, but supporting the survivors through a mental health and psychosocial support lens helps to mitigate these challenges, as highlighted by this case study.